Analysis Of Control Systems Nutrition Hydroponic Crops On Smart Vertical Agriculture - Rasida B R; Cucus A (International Conference on Engineering and Technology Development (ICETD), 2017)
Introduction1.1 BackgroundTechnological developments in the field of agriculture the more years of growing rapidly, Technologyagricultural cultivation by hydroponic system is expected to be an alternative for people who havelimited space or yard, so it can serve as an adequate source of income.Hydroponics is a method of farming by using a planting medium other than soil such as pumice,kerkil, sand, coconut fiber, wood or foam pieces. Hydroponics are there in the community in generalare still using manual systems and relatively costly in terms of time, among others, to measure acidity(pH) and nutrients in plants using plant maintenance hydroponic and determine the volume of waterthat is used to optimize the system that has been realized that , Realizing a temperature regulatingsystem and humidity desirable, but it is still done manually. (Bonorowo, 2014)technique used inhydroponics is NFT (Nutrient FilmTechnique).The basic concept of NFT (NutrientFilmTechnique)is amethod of cultivation with plant roots grow in shallow layers and nutrients to circulate so that theplants can get enough water, nutrients and oxygen